Ecology of Medicinal Plants in Uttarakhand Himalaya, India - Ram, Jeet; Tewari, Beena; Arya, Neeta (Indian Forester, 2010)
Medicinal plants are one of the important components of the forests of Himalaya and grow in different communities and group of species. The herb communities were studied mainly in oak and oak mixed forests of Uttarakhand Himalaya. Herb cover was higher in oak-pine forest while it was lower in oak dominated mixed forest. The most frequent medicinal herb was A. nilagerica while large number of medicinal herbs was rarely distributed in these forests. It was concluded that the natural distribution and their associations would be important for growing and conserving the medicinal herbs in the Uttarakhand Himalaya.